1984
DOI: 10.1002/jsfa.2740350218
|View full text |Cite
|
Sign up to set email alerts
|

Myosin denaturation in pale, soft, and exudative (PSE) porcine muscle tissue as studied by differential scanning calorimetry

Abstract: Myofibrillar tissue from pale, soft, and exudative (PSE) pork was compared to tissue from normal pork by differential scanning calorimetry at pH 5.4. Thermograms of myofibrillar tissue from normal pork were characterised by three major peaks with temperature maxima at 58 and 66"C, associated with myosin denaturation, and at 78"C, associated with actin denaturation. In thermograms of PSE pork, the peak at 58°C was markedly reduced, and appeared as a shoulder. When the thermograms were divided into segments corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
1
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 18 publications
7
36
1
1
Order By: Relevance
“…some denaturation took place [51,52]. It appears that the heat sensitive protein components are somewhat more sensitive also to frozen storage than the actin [53][54][55]. CryoprotectanLs such as a sucrose:sorbitol mixture -due to a protein-carbohydrate/polyol interactionretarded the denaturation process during the frozen storage and probably increased somewhat the denaturation temperature during heating, as has been reported also for egg white proteins [39].…”
Section: -85~mentioning
confidence: 55%
“…some denaturation took place [51,52]. It appears that the heat sensitive protein components are somewhat more sensitive also to frozen storage than the actin [53][54][55]. CryoprotectanLs such as a sucrose:sorbitol mixture -due to a protein-carbohydrate/polyol interactionretarded the denaturation process during the frozen storage and probably increased somewhat the denaturation temperature during heating, as has been reported also for egg white proteins [39].…”
Section: -85~mentioning
confidence: 55%
“…As the ATPase activity of myosin is confined to the head, this suggests that it is the myosin-S1 that is denatured, although Stabursvik et al (1984) suspected that the myosin tail (LMM) could also be involved. Penny (1967a) suggested that in prerigor muscle, myosin (which is bound to actin in the post-rigor myofibril) is more resistant to denaturation by low pH.…”
Section: Myofibrillar Proteins and Myosin Atpase Activitymentioning
confidence: 99%
“…Table 2 lists the denaturation temperature of muscle protein fractions obtained in different studies. DSC and DTA are powerful analytical tools commonly employed to study thermodynamics of protein denaturation [20,33,34]. Three major transitions ( Fig.…”
Section: Thermal Analysis Of Meatmentioning
confidence: 99%
“…This method could be applied for solid meat products. With the use of DSC, investigations on thermal properties of meat proteins from pork, fish, and beef were carried out [20,33,34]. Kinetics of protein denaturation was also studied by a few [35,133,134].…”
Section: Thermal Transitions Of Fat Affecting Stability and Qualitymentioning
confidence: 99%
See 1 more Smart Citation